Comparing the cost-effectiveness of the MPT64-antigen detection test to Xpert MTB/RIF and ZN-microscopy for the diagnosis of Extrapulmonary Tuberculosis: An economic evaluation modelling study. - Shoaib Hassan; Tehmina Mustafa; William Muller; Lisete Torres; Msafiri Marijani; Esther Ngadaya; Sayoki Mfinanga; Yakobo Lema; Erlend Grønningen; Melissa Jorstad; Ole Norheim; Bjarne Robberstad (Public Library of Science (PLoS), 2024)
Extrapulmonary Tuberculosis (EPTB) poses challenges from patient and health system perspectives. The cost-effectiveness analysis of the Xpert MTB/RIF (Xpert) test to diagnose pulmonary tuberculosis is documented. However, there are no economic evaluations for EPTB. Considering the reported better diagnostic sensitivity of the MPT64 test, this study explored its cost-effectiveness as an alternative diagnostic test. We conducted this economic evaluation to assess the cost-effectiveness of the MPT64 test compared to Xpert and ZN microscopy for EPTB adult patients. We utilised a Markov modelling approach to capture short- and long-term costs and benefits from a health system perspective. For the model inputs, we combined data from our cohort studies in Tanzania and peer-reviewed EPTB literature. We calculated the Incremental Cost Effectiveness Ratio (ICER) by comparing the cost (in USD) of each diagnostic test and Quality Adjusted Life Years (QALYs) as health gain. We found the MPT64 test cost-effective for EPTB diagnosis and absolutely dominated ZN microscopy and Xpert using the baseline model inputs. A scenario analysis showed that the Xpert test might be the most cost-effective at its higher test sensitivity, which corresponds to using it to diagnose lymph node aspirates. The prevalence of HIV among EPTB cases, their probability of treatment, costs of ART, and the probability of the MPT64 test in detecting EPTB patients were the main parameters associated with the highest impact on ICER in one-way deterministic analysis. The most cost-effective option for EPTB at the baseline parameters was the MPT64 diagnostic test. Including the MPT64 test in EPTB diagnostic pathways for previously untreated patients can lead to better resource use. The Xpert test was the most cost-effective diagnostic intervention at a higher diagnostic test sensitivity in scenario analyses based on different sites of infection, such as for the lymph node aspirates.